Electrical breakdown of carbon nanotube devices and the predictability of breakdown position - Gopal Krishna Goswami; Karuna Kar Nanda (AIP Advances, 2012)
We have investigated electrical transport properties of long (>10 μm) multiwalled carbon nanotubes (NTs) by dividing individuals into several segments of identical length. Each segment has different resistance because of the random distribution of defect density in an NT and is corroborated by Raman studies. Higher is the resistance, lower is the current required to break the segments indicating that breakdown occurs at the highly resistive segment/site and not necessarily at the middle. This is consistent with the one-dimensional thermal transport model. We have demonstrated the healing of defects by annealing at moderate temperatures or by current annealing. To strengthen our mechanism, we have carried out electrical breakdown of nitrogen doped NTs (NNTs) with diameter variation from one end to the other. It reveals that the electrical breakdown occurs selectively at the narrower diameter region. Overall, we believe that our results will help to predict the breakdown position of both semiconducting and metallic NTs.